Densimetry of diluted aqueous salt solutions and molecular dynamics simulations identify temperature-dependent differences between the hydration of anions and cations - Marta Onuk; Anna Stefaniuk; Iryna Doroshenko; Jarosław Poznański (Scientific Reports)
Abstract This study aims to analyze the temperature-dependent hydration of diluted ionic solutions. Three monovalent anions (Cl-, Br-, and I-), three monovalent cations (Li+, Na+, and K+), and one bivalent ion each (SO4 2- and Mg2+, respectively) were chosen as models. The partial molar volumes of all possible two-component salts (i.e., LiCl, NaCl, KCl, LiBr, NaBr, KBr. LiI, NaI, KI, MgCl2, MgBr2, MgI2, Li2SO4, Na2SO4, K2SO4, and MgSO4) were determined in water at low solute concentrations (10− 3 to 3·10− 2 mol/kg) in the 20 ÷ 40 °C temperature range. The density analysis was based on the first-order (linear) approximation of the density-molality relation corrected for the Debye-Hückel slope for volumes. No additional sophisticated corrections were applied. For all salts except the bivalent-bivalent MgSO4, the partial molar volume is positive and generally increases with temperature much more than bulk water. The temperature-dependent partial molar volumes of particular ions were determined globally, assuming the composition-dependent additive contribution to the partial molar volume of the salt. The qualitative differences between anions and cations were identified, reflecting their divergent electrostatic contributions to solute-solvent interactions. Similar nonlinear trends were observed in molecular dynamics simulations of the solvated separate ions at 10 ÷ 50 °C. The observed differences between anions and cations should be attributed to principal water properties, specifically the electron density distribution, which interferes with the packing of asymmetric water molecules around the ions of interest.